Moderation of gender diversity in factors affecting firm value - Yenny Wati; Layla Hafni; Agus Hocky; Febdwi Suryani; Yanti Mayasari Ginting (Universitas Muhammadiyah Malang, 2024)
Purpose: This study examines the impact of financial performance, board size, and working capital on firm value. Gender diversity is a moderating variable in studies that determines how the effectiveness of financial performance, board size, and working capital affect firm value. Methodology/approach: Manufacturing enterprises are the sample for this research, and the secondary data source is the Indonesian Stock Exchange from 2019 to 2023. This study combines SPSS with a data analysis approach known as moderating regression analysis. Findings: Financial performance, board size, and working capital have a beneficial impact on firm value. Gender diversity can moderate the effects of financial performance, board size, and working capital on the firm's value. Practical and Theoretical Contribution/ Originality: The highest executive levels within the company's hierarchy are the focus of this study. Numerous earlier studies have not been able to examine or test gender diversity in these ranks. Important individuals, such as the board of directors, occupy these positions. This role is crucial to the development and operation of each major business division for the corporation. The study's findings further emphasize the prospective advantages of corporate governance frameworks and gender diversity, which can increase the availability of capital, performance, and value for the firm. Research Limitation: Gender diversity is measured using solely dummy variables and ratios, which ignore the influence of each individual's decision-making style. Gender diversity focuses mostly on business executives. As a result, greater inquiry into other stakeholders who influence business risk-taking decisions is required.